Characterization of Bile Acid Sulfate Conjugates as Substrates of Human Organic Anion Transporting Polypeptides - Orozco, Christine C.; Neuvonen, Mikko; Bi, Yi-An; Cerny, Matthew A.; Mathialagan, Sumathy; Tylaska, Laurie; Rago, Brian; Costales, Chester; King-Ahmad, Amanda; Niemi, Mikko; Rodrigues, A. David (Molecular pharmaceutics, 2023)
Drug interactions involving the inhibition of hepatic organic anion transporting polypeptides (OATPs) 1B1 and OATP1B3 are considered important. Therefore, we sought to study various sulfated bile acids (BA-S) as potential clinical OATP1B1/3 biomarkers. It was determined that BA-S [e.g., glycochenodeoxycholic acid 3-O-sulfate (GCDCA-S) and glycodeoxycholic acid 3-O-sulfate (GDCA-S)] are substrates of OATP1B1, OATP1B3, and sodium-dependent taurocholic acid cotransporting polypeptide (NTCP) transfected into human embryonic kidney 293 cells, with minimal uptake evident for other solute carriers (SLCs) like OATP2B1, organic anion transporter 2, and organic cation transporter 1. It was also shown that BA-S uptake by plated human hepatocytes (PHH) was inhibited (≥96%) by a pan-SLC inhibitor (rifamycin SV), and there was greater inhibition (≥77% versus ≤12%) with rifampicin (OATP1B1/3-selective inhibitor) than a hepatitis B virus myristoylated-preS1 peptide (NTCP-selective inhibitor). Estrone 3-sulfate was also used as an OATP1B1-selective inhibitor. In this instance, greater inhibition was observed with GDCA-S (76%) than GCDCA-S (52%). The study was expanded to encompass the measurement of GCDCA-S and GDCA-S in plasma of SLCO1B1 genotyped subjects. The geometric mean GDCA-S concentration was 2.6-fold (90% confidence interval 1.6, 4.3; P = 2.1 × 10–4) and 1.3-fold (1.1, 1.7; P = 0.001) higher in individuals homozygous and heterozygous for the SLCO1B1 c.521T > C loss-of-function allele, respectively. For GCDCA-S, no significant difference was noted [1.2-fold (0.8, 1.7; P = 0.384) and 0.9-fold (0.8, 1.1; P = 0.190), respectively]. This supported the in vitro data indicating that GDCA-S is a more OATP1B1-selective substrate (versus GCDCA-S). It is concluded that GCDCA-S and GDCA-S are viable plasma-based OATP1B1/3 biomarkers, but they are both less OATP1B1-selective when compared to their corresponding 3-O-glucuronides (GCDCA-3G and GDCA-3G). Additional studies are needed to determine their utility versus more established biomarkers, such as coproporphyrin I, for assessing inhibitors with different OATP1B1 (versus OATP1B3) inhibition signatures.